The Self-Reward sebagai Rasionalisasi Impulsive Buying di TikTok Shop - Dzakiyyah Nisrina (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
This research article examines a phenomenon that is quite popular among Generation Z, namely self-reward, as a cognitive rationalization mechanism that transforms impulsive urges into socially legitimized consumption behaviors within the TikTok Shop ecosystem among Indonesian Generation Z. Using a qualitative approach based on a literature review with Jean Baudrillard’s theory of the consumer society as the primary analytical framework, this study identifies two key issues: first, how the self-reward narrative functions as a rationalization mechanism for impulsive buying behavior; and second, how the design of the TikTok Shop platform systematically creates conditions that facilitate the activation of this narrative. The analysis reveals that self-reward has undergone a significant shift in meaning from achievement-based self-appreciation to desire-based consumerist justification through four cognitive stages: emotional stimulus, cognitive conflict, moral licensing activation, and post-hoc rationalization. From a Baudrillardian perspective, consumption on TikTok Shop is no longer functional but rather semiotic, where purchases serve as expressions of identity and social differentiation. Platform designs such flash sales,live streaming, scarcity framing, the FYP algorithm, and the pay feature synergistically create an ecosystem that shortens consumers’ reflective pauses and reinforces a cycle of impulsive buying that is difficult to break.